EXPLORING PARENTLESS CHILDREN’S EXPERIENCES IN ISLAMIC CHARACTER BUILDING AT THE ‘DIAMOND’ POLICE STATION - Safitri, Asyifa Annur; Rijalul Alam, Naufal Ahmad (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
The loss of parental roles whether due to death, divorce, incarceration, or emotional neglect poses serious challenges to children’s character development. This study explores the moral and emotional impacts of such loss on children involved in legal cases under the jurisdiction of the Diamond Police Station, and identifies the support factors that contribute to their resilience. Using a qualitative case study approach, four children who had experienced the absence of one or both parents were interviewed. Thematic analysis based on moral development theory revealed negative effects on moral knowledge, emotions, and actions, including emotional neglect, identity confusion, and low self-esteem. However, external support from schools, religious institutions, peer groups, and community systems contributed to self-regulation and moral growth. This study highlights the need for integrated psychosocial interventions and the importance of inclusive environments. As a response to these conditions, the Diamond Police Station serves as an innovative example of Islamic educational institution management, providing moral guidance and psychosocial support in a non-formal context. This demonstrates that community based institutions can play a vital role in fostering resilience and moral development among children who have lost parental support.